MXene material composite nickel-iron-manganese-based positive electrode material and preparation method and application thereof

Through the nano-scale MXene material composited with O3 nickel ferromanganese-based positive electrode material, the problems of sodium ion deintercalation and electrolyte decomposition of O3 material at high voltage are solved, the air stability and cycle life of the battery are improved, and the high air conditioning and circulation life of the battery are achieved Capacity and stable electrochemical properties.

CN119153640APending Publication Date: 2024-12-17HUNAN NANENG TIMES TECH DEV CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311776114.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-21
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

O3 layered transition metal oxide positive electrode material can easily lead to sodium ion deintercalation, material microcracks and electrolyte decomposition at high voltages, affecting battery capacity and life.

Method used

Nano-scale two-dimensional MXene material is used to combine with O3 type nickel ferromanganese-based positive electrode material to reduce sodium ion removal and electrolyte reaction, enhance mechanical strength and electronic conductivity, and form a stable interface film.

Benefits of technology

The air stability and cycle life of the material are significantly improved, high capacity and electrochemical properties are maintained, the discharge specific capacity reaches 155.86mAh g-1, and the capacity retention rate of 100 cycles is 86.47%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153640A_ABST
    Figure CN119153640A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of battery materials, and particularly relates to an MXene material composite nickel-iron-manganese-based positive electrode material and a preparation method and application thereof. The chemical formula of the MXene material composite nickel-iron-manganese-based positive electrode material is NaNiaFebMncTMdO2 (at) MXene, TM is one or more of Mg, Al, Ti, Zn, Zr, Cu, Nb, W and Mo, values of a, b, c and d depend on charge balance, M in MXene is one or more of Ti, Nb, V, Mo, Ta, Cr and Hf, X is C or N, and ene represents a structural unit of graphene. MXene is compounded with the nickel-iron-manganese-based positive electrode material, so that the situation that the nickel-iron-manganese-based positive electrode material is in contact with water and CO2 in air to inhibit the interface side reaction between electrolyte and the nickel-iron-manganese-based material can be reduced, and excellent cycling stability is shown under high voltage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and in particular relates to a MXene material composite nickel-iron-manganese-based positive electrode material and a preparation method and application thereof. Background Art

[0002] With the growing demand for electronic devices and electric vehicles, lithium-ion batteries have been widely used as important energy storage devices. However, due to the shortage, high cost and uneven distribution of lithium resources, while sodium resources are abundant, easy to obtain and low cost, sodium-ion battery technology has developed rapidly, and the industrialization process in the fields of energy storage and small power is also advancing rapidly.

[0003] At present, the positive electrode materials of sodium ion batteries can be divided into layered oxides, Prussian blue and polyanions, among which layered transition metal oxide positive electrode materials have high energy density and compaction density, and have a similar synthesis route to lithium battery ternary materials, and are considered to be more ideal positive electrode materials for sodium ion batteries. O3-type materials have the advantages of high initial sodium content and high capacity, and are a research hotspot for commercial applications. However, the bulk phase of O3-type layered transition metal oxide materials has a large sodium ion content and a large sodium interlayer spacing, which makes the material easy to react with water and carbon dioxide in the air, and sodium ions are released from the bulk phase, resulting in high residual alkali on the surface of the material, affecting the processing and cycle performance of the material. Although the energy density of the material can be significantly improved when charged to above 4.1V, under high voltage (above 4.1V), due to the deep sodium ion deintercalation of the material, the anisotropy of the single unit cell increases, resulting in microcracks in the material. In addition, high voltage will also cause the decomposition of the electrolyte, resulting in an increase in the interface resistance between the O3-type material and the electrolyte, resulting in serious battery capacity decay, and the battery life is far from meeting the actual needs. Summary of the invention

[0004] In order to overcome the problems in the prior art, the present invention uses two-dimensional MXene and O3-type nickel-iron-manganese-based cathode materials for compounding, and uses a nano-scale thin layer of two-dimensional MXene material as an intermediate layer to reduce the contact between the O3-type nickel-iron-manganese-based cathode material and water and CO2 in the air, inhibit the release of sodium ions from the bulk phase, and improve the air stability of the material. At the same time, due to the unique thin layer structure of the MXene material, it can be tightly coated on the surface of the material, which can significantly increase the mechanical strength of the particles and reduce the generation of microcracks during the cycle.

[0005] In order to achieve the above object, the embodiment of the present invention provides a MXene material composite nickel-iron-manganese-based positive electrode material, the chemical formula of the MXene material composite nickel-iron-manganese-based positive electrode material is: NaNi a Fe b Mn c TM d O2 @MXene, where TM is one or more of Mg, Al, Ti, Zn, Zr, Cu, Nb, W, and Mo, where the values ​​of a, b, c, and d depend on the charge balance, M in MXene is one or more of Ti, Nb, V, Mo, Ta, Cr, and Hf, X is C or N, and ene represents the structural unit of graphene.

[0006] In one embodiment, the MXene material is a single-layer sheet structure with an electrical conductivity exceeding 3000 S cm -1 .

[0007] The present invention also provides a method for preparing the above-mentioned MXene material composite nickel-iron-manganese-based positive electrode material, comprising the following steps:

[0008] S1. Add a precipitant and a complexing agent to a solution of a stoichiometric ratio of a manganese salt, a nickel salt, an iron salt and a TM salt under a protective atmosphere, obtain a hydroxide precursor after a coprecipitation reaction, and then sinter the precursor with a sodium salt at a high temperature to obtain a nickel-iron-manganese-based positive electrode material;

[0009] S2, adding fluoride salt to an acidic solution, and slowly adding MAX phase material, heating in a water bath for reaction, centrifuging and washing to obtain a mixture material, ultrasonically dispersing the mixture material, and then centrifuging to obtain a solid and drying it to obtain a MXene material;

[0010] S3. Add the nickel-iron-manganese-based positive electrode material and MXene material into a solvent for ultrasonic dispersion, stir under constant temperature conditions, and evaporate to dryness to obtain a MXene material composite nickel-iron-manganese-based positive electrode material.

[0011] In one of the embodiments, in step S1, the TM salt is one or more of soluble sulfates, oxalates, acetates, nitrates or chlorides of Mg, Al, Ti, Zn, Zr, Cu, Nb, W, and Mo; the high-temperature sintering temperature is 800-900°C, and the sintering time is 6-20h.

[0012] In one embodiment, in step S2, the fluoride salt is one or more of LiF, NaF, and KF; the acidic solution is HCl, H 2 SO 4 , HNO 3 One or more of the solutions; the mass ratio of the fluoride salt to the MAX material is 1:(0.1-10), and the liquid-to-solid ratio of the acidic solution MAX material is (1-20):1.

[0013] In one embodiment, in step S2, the temperature of the water bath heating reaction is 25-95°C and the time is 4-48 hours; the pH of the centrifugal washing process is 6.8-7.

[0014] In one of the embodiments, in step S3, the mass ratio of the nickel-iron-manganese-based positive electrode material to the MXene material is 1:(0.001-0.05); the solvent is one or more of deionized water, ethanol, ethylene glycol, and acetone; the liquid-to-solid ratio of the nickel-iron-manganese-based positive electrode material and the MXene material to the solvent is (10-100):1.

[0015] In one embodiment, the ultrasonic dispersion time is 0.5-5h; the stirring treatment under constant temperature conditions is performed at a temperature of 40-80°C for a time of 4 to 24h.

[0016] Based on the same inventive concept, an embodiment of the present invention further provides a positive electrode plate, which includes a current collector and an active layer located on the surface of the current collector, and the active layer includes a nickel-iron-manganese-based positive electrode material composited with the above-mentioned MXene material.

[0017] Based on the same inventive concept, an embodiment of the present invention further provides a sodium ion battery, which includes the above-mentioned positive electrode plate.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) The nickel-iron-manganese-based positive electrode material composited with the MXene material of the present invention uses a nano-thin layer of two-dimensional MXene material as an intermediate layer to reduce the O3-type nickel-iron-manganese-based positive electrode material and water and CO in the air. 2 contact, inhibiting the escape of sodium ions from the bulk phase and improving the air stability of the material. The unique thin layer structure of MXene material can be tightly coated on the surface of the material, significantly increasing the mechanical strength of the particles and reducing the generation of microcracks during the cycle. At the same time, it can also inhibit the interfacial side reactions between the electrolyte and the O3-type nickel-iron-manganese-based positive electrode material, reducing the decomposition of the electrolyte and the erosion of the electrolyte on the material, and preventing the material structure from being destroyed from the outside to the inside, thereby improving the cycle life of the battery. Since the MXene material is a nano-scale thin layer, the discharge capacity of the material will not be reduced after the composite due to the excessive thickness of the coating layer; at the same time, it can enhance the electronic conductivity of the O3-type nickel-iron-manganese-based positive electrode material, and can give full play to the electrochemical properties of the material during the charge and discharge process. The interface modified by the MXene material can form a more stable CEI film during the charge and discharge process, thereby reducing the interface impedance and providing a higher capacity. In the voltage range of 2-4.1V, the discharge capacity of the material at a current rate of 0.1C can reach 155.86mAh g -1 The material still has a capacity retention rate of 86.47% after 100 cycles at a current rate of 1C.

[0020] (2) The preparation method of the MXene material composite nickel-iron-manganese-based positive electrode material of the present invention includes the steps of co-precipitation, high-temperature sintering, ultrasound and centrifugation. The raw materials are easily available, the synthesis method is simple and easy to operate, the synthesis cycle is short, and it is easy to realize industrial production; and the battery prepared using the positive electrode material is safe, effective, economical and environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 SEM images of the positive electrode materials provided by the present invention, wherein Figure (a) is a nickel-iron-manganese-based positive electrode material composited with MXene material prepared in Example 1, and Figure (b) is a pure phase nickel-iron-manganese-based positive electrode material prepared in Comparative Example 1;

[0023] Figure 2 A comparison chart of the charge and discharge curves of the nickel-iron-manganese-based positive electrode composited with the MXene material prepared in Example 1 of the present invention and the pure phase nickel-iron-manganese and positive electrode material prepared in Comparative Example 1 in the range of 2-4.1V;

[0024] Figure 3 A comparison chart of the cycling performance of the nickel-iron-manganese-based positive electrode composited with the MXene material prepared in Example 1 of the present invention and the pure phase nickel-iron-manganese and positive electrode material prepared in Comparative Example 1 at a current rate of 1C;

[0025] Figure 4 The SEM images of the positive electrode materials provided by the present invention after 100 cycles, wherein Figure (a) is the nickel-iron-manganese-based positive electrode composited with MXene material prepared in Example 1, and Figure (b) is the pure phase nickel-iron-manganese-based positive electrode material prepared in Comparative Example 1. DETAILED DESCRIPTION

[0026] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0027] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0028] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0029] In order to reduce the O3 type nickel-iron-manganese based cathode material and the water and CO 2 The present invention uses a two-dimensional MXene material and a nickel-iron-manganese-based positive electrode material to composite to obtain a composite positive electrode material, whose chemical formula is: NaNi a Fe b Mn c TM d O 2 @MXene, where TM is a doping element, specifically including one or more of Mg, Al, Ti, Zn, Zr, Cu, Nb, W, and Mo, where the values ​​of a, b, c, and d depend on the charge balance. M in the MXene material represents one or more of Ti, Nb, V, Mo, Ta, Cr, and Hf, X is C or N, and ene represents the structural unit of graphene. MXene materials specifically include Ti 3 C 2 、V 3 C 2 , Nb 2 C.Mo 2 C. Zr 3 C 2 , Mn 3 N 2 MXene materials are single-layer flake structures with electrical conductivity exceeding 3000S cm -1 . After being compounded with O3-type nickel-iron-manganese-based cathode materials, their conductivity can be enhanced, and the electrical properties of the materials can be more fully utilized during the charge and discharge process. The interface modified by the MXene material can form a more stable CEI film during the charge and discharge process, thereby reducing the interface impedance and providing higher capacity. The single-layer structure of the MXene material can be tightly coated on the surface of the O3-type nickel-iron-manganese-based cathode material, increasing the mechanical strength of the particles and reducing the generation of microcracks during the cycle; at the same time, it inhibits the interface side reaction between the electrolyte and the O3-type nickel-iron-manganese-based cathode material, reduces the decomposition of the electrolyte and the erosion of the electrolyte on the material, and prevents the material structure from being destroyed from the outside to the inside, thereby improving the cycle life of the battery.

[0030] The preparation method of MXene material composite nickel-iron-manganese-based positive electrode material specifically comprises the following steps:

[0031] S1. Add precipitant and complexing agent to the solution of manganese salt, nickel salt, iron salt and TM salt in stoichiometric ratio under protective atmosphere, obtain hydroxide precursor after coprecipitation reaction, and then sinter the precursor with sodium salt at high temperature to obtain nickel-iron-manganese-based positive electrode material. Among them, TM salt is one or more of soluble sulfate, oxalate, acetate, nitrate or chloride of Mg, Al, Ti, Zn, Zr, Cu, Nb, W, Mo; precipitant is one or more of sodium hydroxide, potassium hydroxide, barium hydroxide, sodium carbonate, lithium hydroxide; complexing agent is one or more of ammonia water, ammonium bicarbonate, ethylenediamine, ethylenediaminetetraacetic acid (EDTA), sodium citrate or oxalic acid; process parameters of coprecipitation reaction: pH is adjusted to 10-12, reaction time is 10-30h. After coprecipitation reaction, solid-liquid separation, repeated washing and impurity removal and drying treatment are performed to obtain hydroxide precursor. The high-temperature sintering process is controlled at a temperature of 800-900℃, and the sintering time is 6-20h.

[0032] S2, adding fluoride salt to the acidic solution, and slowly adding MAX phase material, heating in a water bath for reaction, centrifuging and washing to obtain a mixture material, ultrasonically dispersing the mixture material, and then centrifuging and drying the solid to obtain MXene material. In this process, the fluoride salt is LiF, NaF, KF, CsF, CaF 2 One or more of the following; the acidic solution is HCl, H 2 SO 4 , HNO 3 One or more in solution; MAX phase material is Ti 2 AlC,Ti 3 AlC 2 、V 2 AlC、Nb 2 AlC、Cr 2 AlC、Mo 2 GaC、Ti 2 AlN and other materials. The mass ratio of fluoride salt to MAX material is 1: (0.1-10), and the liquid-solid ratio of the acidic solution to the fluoride salt and MAX material is (1-20): 1. The water bath heating reaction temperature is 25-95°C, and the time is 4-48h; the pH of the centrifugal washing process is 6.8-7.

[0033] S3. After adding the nickel-iron-manganese-based cathode material and MXene material to the solvent for ultrasonic dispersion, stirring is performed under constant temperature conditions, and evaporation is performed to obtain a MXene material composite nickel-iron-manganese-based cathode material. In this process, the mass ratio of the nickel-iron-manganese-based cathode material to the MXene material is 1: (0.001-0.05); the solvent is one or more of deionized water, ethanol, ethylene glycol, and acetone; the liquid-solid ratio of the nickel-iron-manganese-based cathode material and the MXene material to the solvent is (10-100): 1. The ultrasonic dispersion time is 0.5-5h; the temperature during the stirring treatment under the constant temperature conditions is 40-80°C.

[0034] The embodiment of the present invention also provides a positive electrode plate, comprising a current collector and an active layer located on the surface of the current collector, wherein the active layer comprises the nickel-iron-manganese-based positive electrode material composited with the above-mentioned MXene material. The above-mentioned pole plates can also be assembled to obtain a sodium battery with excellent performance.

[0035] The above introduces the specific implementation methods of the present application. In order to objectively illustrate the technical effects produced by the present application, the following examples and comparative examples will be used for description.

[0036] Example 1

[0037] A MXene material composite nickel-iron-manganese-based positive electrode material and a preparation method thereof, comprising the following steps:

[0038] (1) NiSO 4 7H 2 O,FeSO 4 7H 2 O,MnSO 4 ·H 2 O was dissolved in deionized water at a molar ratio of 3:3:3 to prepare 2 mol L -1 The transition metal ion solution was then added to a continuous stirred tank reactor under nitrogen atmosphere, and 4 mol L -1 NaOH precipitant and 20 wt% NH 3 ·H 2 After the complexing agent O is added, the pH of the solution is kept in the range of 10-11. After sufficient reaction, it is filtered and washed repeatedly to remove impurities. After drying, Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH) 2 Precursor, Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH) 2 with Na 2 CO 3The mixture was prepared according to a molar ratio of 1:0.52 and sintered at 870 °C for 16 h in an oxygen atmosphere to obtain NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 Positive electrode material.

[0039] (2) Add 1g NaF to 40mL (9m) hydrochloric acid solution, and then add 1g Ti in a 1:1 mass ratio of fluoride salt to MAX material. 3 AlC 2 The material was stirred in a water bath at 45°C for 24 hours. Then, it was centrifuged and washed with water and ethanol respectively until the pH of the supernatant was 7 to obtain a MXene precursor. The MXene precursor was ultrasonically dispersed in water for 1 hour and centrifuged to obtain a single layer of Ti 3 C 2 Material.

[0040] (3) Ti 3 C 2 With NaNi 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2 Add it into deionized water at a mass ratio of 1:50, control the liquid-to-solid ratio of the system to 1:20, ultrasonicate for 0.5h, stir in a water bath at 80℃ until the solution is completely evaporated, and obtain the nickel-iron-manganese-based positive electrode material NaNi composited with MXene material 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2@ Ti 3 C 2 .

[0041] Example 2

[0042] A MXene material composite nickel-iron-manganese-based positive electrode material and a preparation method thereof, comprising the following steps:

[0043] (1) NiSO 4 7H 2 O,FeSO 4 7H 2 O,MnSO 4 ·H 2 O, ZnSO 4 Dissolve in deionized water at a molar ratio of 3:2:3:1 to prepare 2 mol L -1 The transition metal ion solution was then added to a continuous stirred tank reactor under nitrogen atmosphere, and 4 mol L -1 NaOH precipitant and 20 wt% NH3 ·H 2 After the complexing agent O is added, the pH of the solution is kept in the range of 10-11. After sufficient reaction, it is filtered and washed repeatedly to remove impurities. After drying, Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Zn 1 / 9 (OH) 2 Precursor, Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Zn 1 / 9 (OH) 2 with Na 2 CO 3 The mixture was prepared according to a molar ratio of 1:0.52 and sintered at 930 °C for 16 h in an oxygen atmosphere to obtain NaNi 1 / 3 Fe 2 / 9 Mn 1 / 3 Zn 1 / 9 O 2 Positive electrode material.

[0044] (2) Add 1 g of LiF to 40 mL (9 m) sulfuric acid solution, and then add 10 g of Ti in a mass ratio of fluoride salt to MAX material of 1:10. 3 AlC 2 The material was stirred in a water bath at 60°C for 24 hours. Then, it was centrifuged and washed with water and ethanol respectively until the pH of the supernatant was 7 to obtain a MXene precursor. The MXene precursor was ultrasonically dispersed in water for 1 hour and centrifuged to obtain a single layer of Ti 3 C 2 Material.

[0045] (3) Ti 3 C 2 With NaNi 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2 Add it into deionized water at a mass ratio of 1:100, control the liquid-to-solid ratio of the system to 1:50, ultrasonicate for 1h, stir in a 45℃ water bath until the solution is completely evaporated, and obtain the nickel-iron-manganese-based positive electrode material NaNi composited with MXene material 1 / 3 Fe 2 / 9 Mn 1 / 3 Zn 1 / 9 O 2@ Ti 3 C 2 .

[0046] Example 3

[0047] A MXene material composite nickel-iron-manganese-based positive electrode material and a preparation method thereof, comprising the following steps:

[0048] (1) NiSO 4 7H 2 O,FeSO 4 7H 2 O,MnSO 4 ·H 2 O,CuSO 4 Dissolve in deionized water at a molar ratio of 3:2:3:1 to prepare 2 mol L -1 The transition metal ion solution was then added to a continuous stirred tank reactor under nitrogen atmosphere, and 4 mol L -1 NaOH precipitant and 20 wt% NH 3 ·H 2 After the complexing agent O is added, the pH of the solution is kept in the range of 10-11. After sufficient reaction, it is filtered and washed repeatedly to remove impurities. After drying, Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 Precursor, Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 with Na 2 CO 3 The mixture was prepared according to a molar ratio of 1:0.52 and sintered at 870 °C for 16 h in an oxygen atmosphere to obtain NaNi 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2 Positive electrode material.

[0049] (2) Add 1g NaF to 40mL (9m) hydrochloric acid solution, and then add 1g V according to the mass ratio of fluoride salt to MAX material of 1:1. 2 AlC material was stirred in a water bath at 45°C for 24 hours. Then it was centrifuged and washed with water and ethanol respectively until the pH of the supernatant was 7 to obtain a MXene precursor. The MXene precursor was ultrasonically dispersed in water for 1 hour and centrifuged to obtain a single layer of V 3 C 2 Material.

[0050] (3) V 3 C 2 With NaNi 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu1 / 9 O 2 Add it into deionized water at a mass ratio of 1:100, control the liquid-to-solid ratio of the system to 1:50, ultrasonicate for 1h, stir in a 45℃ water bath until the solution is completely evaporated, and obtain the nickel-iron-manganese-based positive electrode material NaNi composited with MXene material 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2@ V 3 C 2 .

[0051] Example 4

[0052] A MXene material composite nickel-iron-manganese-based positive electrode material and a preparation method thereof, comprising the following steps:

[0053] (1) NiSO 4 7H 2 O,FeSO 4 7H 2 O,MnSO 4 ·H 2 O was dissolved in deionized water at a molar ratio of 3:3:3 to prepare 2 mol L -1 The transition metal ion solution was then added to a continuous stirred tank reactor under nitrogen atmosphere, and 4 mol L -1 NaOH precipitant and 20 wt% NH 3 ·H 2 After the complexing agent O is added, the pH of the solution is kept in the range of 10-11. After sufficient reaction, it is filtered and washed repeatedly to remove impurities. After drying, Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH) 2 Precursor, Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 (OH) 2 with Na 2 CO 3 The mixture was prepared according to a molar ratio of 1:0.52 and sintered at 870 °C for 16 h in an oxygen atmosphere to obtain NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 Positive electrode material.

[0054] (2) Add 1g NaF to 40mL (9m) hydrochloric acid solution, and then add 1g Ti in a 1:1 mass ratio of fluoride salt to MAX material. 3 AlC 2The material was stirred in a water bath at 45°C for 24 hours. Then, it was centrifuged and washed with water and ethanol respectively until the pH of the supernatant was 7 to obtain a MXene precursor. The MXene precursor was ultrasonically dispersed in water for 1 hour and centrifuged to obtain a single layer of Ti 3 C 2 Material.

[0055] (3) Ti 3 C 2 With NaNi 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2 Add it into deionized water at a mass ratio of 1:50, control the liquid-to-solid ratio of the system to 1:20, ultrasonicate for 0.5h, stir in a water bath at 80℃ until the solution is completely evaporated, and obtain the nickel-iron-manganese-based positive electrode material NaNi composited with MXene material 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2@ Ti 3 C 2 .

[0056] Comparative Example 1

[0057] A method for preparing a pure phase sodium nickel iron manganese oxide positive electrode material comprises the following steps:

[0058] NiSO 4 7H 2 O,FeSO 4 7H 2 O,MnSO 4 ·H 2 O,CuSO 4 Dissolve in deionized water at a molar ratio of 3:2:3:1 to prepare 2 mol L -1 The transition metal ion solution was then added to a continuous stirred tank reactor under nitrogen atmosphere, and 4 mol L -1 NaOH precipitant and 20 wt% NH 3 ·H 2 After the complexing agent O is added, the pH of the solution is kept in the range of 10-11. After sufficient reaction, it is filtered and washed repeatedly to remove impurities. After drying, Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 Precursor, Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH)2 with Na 2 CO 3 The mixture was prepared according to a molar ratio of 1:0.52 and sintered at 870 °C for 16 h in an oxygen atmosphere to obtain NaNi 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2 Positive electrode material.

[0059] Comparative Example 2

[0060] A MXene material composite nickel-iron-manganese-based positive electrode material and a preparation method thereof, comprising the following steps:

[0061] (1) NiSO 4 7H 2 O,FeSO 4 7H 2 O,MnSO 4 ·H 2 O,CuSO 4 Dissolve in deionized water at a molar ratio of 3:2:3:1 to prepare 2 mol L -1 The transition metal ion solution was then added to a continuous stirred tank reactor under nitrogen atmosphere, and 4 mol L -1 NaOH precipitant and 20 wt% NH 3 ·H 2 After the complexing agent O is added, the pH of the solution is kept in the range of 10-11. After sufficient reaction, it is filtered and washed repeatedly to remove impurities. After drying, Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 Precursor, Ni 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 (OH) 2 with Na 2 CO 3 The mixture was prepared according to a molar ratio of 1:0.52 and sintered at 870 °C for 16 h in an oxygen atmosphere to obtain NaNi 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2 Positive electrode material.

[0062] (2) Add 1g NaF to 40mL (9m) hydrochloric acid solution, and then add 1g Ti in a 1:1 mass ratio of fluoride salt to MAX material. 3 AlC 2The material was stirred in a water bath at 45°C for 24 hours. Then, it was centrifuged and washed with water and ethanol respectively until the pH of the supernatant was 7 to obtain a MXene precursor. The MXene precursor was ultrasonically dispersed in water for 1 hour and centrifuged to obtain a single layer of Ti 3 C 2 Material.

[0063] (3) Ti 3 C 2 With NaNi 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2 Add it into deionized water at a mass ratio of 1:5, control the liquid-to-solid ratio of the system to 1:10, ultrasonicate for 1h, stir in a 45℃ water bath until the solution is completely evaporated, and obtain the nickel-iron-manganese-based positive electrode material NaNi composited with MXene material 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2@ Ti 3 C 2 .

[0064] Spectral analysis

[0065] The positive electrode materials obtained in the examples and comparative examples and the materials after cycling were subjected to SEM analysis. Taking Example 1 and Comparative Example 1 as examples, the SEM images of the prepared MXene material composite nickel-iron-manganese-based positive electrode material and the pure phase sodium nickel-iron-manganese oxide positive electrode material are as follows: Figure 1 As shown, Figure 1 In (a), NaNi 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2@ Ti 3 C 2 The particle size is about 5μm, and the surface is covered with a thin film, indicating that the MXene material is successfully composited on the nickel-iron-manganese-based positive electrode material. Figure 1 (b) NaNi 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2 The particle size of the material is about 5μm, the surface of the material is smooth, and it is a pure phase material. The SEM spectrum of the material after cycling is as follows Figure 4 As shown, Figure 4 (a) is NaNi 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O2@ Ti 3 C 2 After the cycle, the particles are intact and spherical in structure; Figure 4 (b) is NaNi 1 / 3 Fe 2 / 9 Mn 1 / 3 Cu 1 / 9 O 2 Spectrum of the material after recycling, with obvious cracks appearing on the particles.

[0066] Electrical performance analysis

[0067] Battery assembly: Weigh 0.2000g of the positive electrode material prepared in the embodiment and comparative example, add 0.0250g of conductive carbon black as a conductive agent and 0.0250g of PVDF (polyvinylidene fluoride) as a binder, mix well and apply on aluminum foil to make a positive electrode sheet, and assemble into a CR2025 button battery in a vacuum glove box with a metal sodium sheet as the negative electrode, a Whatman GF / D glass fiber diaphragm as the battery separator, and 1mol / L NaClO4 (EC:DMC=1:1 (volume ratio) + 5% FEC) as the electrolyte. After the materials are assembled into a half-cell, the electrochemical performance test is carried out in the range of 2-4.1V. At a current rate of 0.1C, the first coulomb efficiency, discharge specific capacity and capacity retention rate after 100 cycles at a current rate of 1C are measured. The results are as follows. Taking the embodiment and comparative example 1 as comparison, the charge and discharge curves of the comparative example in the range of 2-4.1V and the cycle performance comparison at a current rate of 1C are as follows. Figure 2 , 3 shown.

[0068] Table 1 Battery electrical performance test results corresponding to the positive electrode materials obtained in the examples and comparative examples

[0069]

[0070] It can be seen from the above table that compared with pure phase positive electrode materials, MXene material composites can avoid direct contact between nickel-iron-manganese-based positive electrode materials and air and electrolytes. While enhancing the mechanical strength of nickel-iron-manganese-based materials, it can also improve the electronic conductivity of the materials, making the materials have better cycle stability. Higher electronic conductivity can ensure that the materials can achieve a higher discharge specific capacity.

[0071] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.

Claims

1. A MXene material composite nickel-iron-manganese-based positive electrode material, characterized in that: The chemical formula of the MXene material composite nickel-iron-manganese-based positive electrode material is: NaNi a Fe b Mn c TM d O2@MXene, where TM is one or more of Mg, Al, Ti, Zn, Zr, Cu, Nb, W, and Mo, where the values ​​of a, b, c, and d depend on the charge balance, M in MXene is one or more of Ti, Nb, V, Mo, Ta, Cr, and Hf, X is C or N, and ene represents the structural unit of graphene.

2. The MXene material composite nickel-iron-manganese-based positive electrode material according to claim 1, characterized in that: The MXene material has a single-layer flake structure and an electrical conductivity of more than 3000 S cm -1 .

3. The method for preparing a MXene material composite nickel-iron-manganese-based positive electrode material according to any one of claims 1-2, characterized in that: The following steps are involved: S1. Add a precipitant and a complexing agent to a solution of a stoichiometric ratio of a manganese salt, a nickel salt, an iron salt and a TM salt under a protective atmosphere, obtain a hydroxide precursor after a coprecipitation reaction, and then sinter the precursor with a sodium salt at a high temperature to obtain a nickel-iron-manganese-based positive electrode material; S2, adding fluoride salt to an acidic solution, and slowly adding MAX phase material, heating in a water bath for reaction, centrifuging and washing to obtain a mixture material, ultrasonically dispersing the mixture material, and then centrifuging to obtain a solid and drying it to obtain a MXene material; S3. Add the nickel-iron-manganese-based positive electrode material and MXene material into a solvent for ultrasonic dispersion, stir under constant temperature conditions, and evaporate to dryness to obtain a MXene material composite nickel-iron-manganese-based positive electrode material.

4. The method for preparing the MXene material composite nickel-iron-manganese-based positive electrode material according to claim 3, characterized in that: In step S1, the TM salt is one or more of soluble sulfates, oxalates, acetates, nitrates or chlorides of Mg, Al, Ti, Zn, Zr, Cu, Nb, W, and Mo; the high-temperature sintering temperature is 800-900°C, and the sintering time is 6-20h.

5. The method for preparing the MXene material composite nickel-iron-manganese-based positive electrode material according to claim 3, characterized in that: In step S2, the fluoride salt is one or more of LiF, NaF, and KF; the acidic solution is one or more of HCl, H2SO4, and HNO3 solutions; the mass ratio of the fluoride salt to the MAX material is 1:(0.1-10), and the liquid-to-solid ratio of the acidic solution to the MAX material is (1-20):

1.

6. The method for preparing the MXene material composite nickel-iron-manganese-based positive electrode material according to claim 3, characterized in that: In step S2, the temperature of the water bath heating reaction is 25-95°C for 4-48 hours; the pH of the centrifugal washing process is 6.8-7.

7. The method for preparing the MXene material composite nickel-iron-manganese-based positive electrode material according to claim 3, characterized in that: In step S3, the mass ratio of the nickel-iron-manganese-based positive electrode material to the MXene material is 1:(0.001-0.05); the solvent is one or more of deionized water, ethanol, ethylene glycol, and acetone; the liquid-solid ratio of the nickel-iron-manganese-based positive electrode material and the MXene material to the solvent is (10-100):

1.

8. The method for preparing the MXene material composite nickel-iron-manganese-based positive electrode material according to claim 3, characterized in that: The ultrasonic dispersion time is 0.5-5h; the stirring treatment under the constant temperature condition is carried out at a temperature of 40-80°C for a time of 4-24h.

9. A positive electrode sheet, characterized in that: The positive electrode plate includes a current collector and an active layer located on the surface of the current collector, and the active layer includes a nickel-iron-manganese-based positive electrode material composited with the MXene material described in any one of claims 1-2.

10. A sodium ion battery, characterized in that: The sodium ion battery comprises the positive electrode sheet as described in claim 9.

Citation Information

Cited By

  • Composite positive electrode material, preparation method thereof and sodium ion battery

    CN119695120A

  • Composite positive electrode material, preparation method thereof and sodium ion battery

    CN119695120B